Esketamine Nasal Spray Plus Oral Antidepressant in Patients With Treatment-Resistant Depression - Wajs, Ewa; Aluisio, Leah; Holder, Richard; Daly, Ella J.; Lane, Rosanne; Lim, Pilar; George, Joyce E.; Morrison, Randall L.; Sanacora, Gerard; Young, Allan H.; Kasper, Siegfried; Sulaiman, Ahmad Hatim; et al. (Physicians Postgraduate Press, 2020)
OBJECTIVE: To evaluate long-term safety and efficacy of esketamine nasal spray plus a new oral antidepressant (OAD) in patients with treatment-resistant depression (TRD). METHODS: This phase 3, open-label, multicenter, long-term (up to 1 year) study was conducted between October 2015 and October 2017. Patients (≥ 18 years) with TRD (DSM-5 diagnosis of major depressive disorder and nonresponse to ≥ 2 OAD treatments) were enrolled directly or transferred from a short-term study (patients aged ≥ 65 years). Esketamine nasal spray (28-mg, 56-mg, or 84-mg) plus new OAD was administered twice a week in a 4-week induction (IND) phase and weekly or every-other-week for patients who were responders and entered a 48-week optimization/maintenance (OP/MAINT) phase. RESULTS: Of 802 enrolled patients, 86.2% were direct-entry and 13.8% were transferred-entry; 580 (74.5%) of 779 patients who entered the IND phase completed the phase, and 150 (24.9%) of 603 who entered the OP/MAINT phase completed the phase. Common treatment-emergent adverse events (TEAEs) were dizziness (32.9%), dissociation (27.6%), nausea (25.1%), and headache (24.9%). Seventy-six patients (9.5%) discontinued esketamine due to TEAEs. Fifty-five patients (6.9%) experienced serious TEAEs. Most TEAEs occurred on dosing days, were mild or moderate in severity, and resolved on the same day. Two deaths were reported; neither was considered related to esketamine. Cognitive performance generally either improved or remained stable postbaseline. There was no case of interstitial cystitis or respiratory depression. Treatment-emergent dissociative symptoms were transient and generally resolved within 1.5 hours postdose. Montgomery-Åsberg Depression Rating Scale total score decreased during the IND phase, and this reduction persisted during the OP/MAINT phase (mean [SD] change from baseline of respective phase to endpoint: IND, -16.4 [8.76]; OP/MAINT, 0.3 [8.12]). CONCLUSIONS: Long-term esketamine nasal spray plus new OAD therapy had a manageable safety profile, and improvements in depression appeared to be sustained in patients with TRD. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT02497287. © Copyright 2020 Physicians Postgraduate Press, Inc.